Erratum: Khanjani, M., Yazyanpanah, S., Ostovan, H. & Fayaz, B.A. (2012) Three new species of the genus Tycherobius Bolland (Acari: Camerobiidae) from Iran. Zootaxa 3266: 23–40 - Khanjani, M.; Yazyanpanah, S.; Ostovan, H.; Fayaz, B. A. (Zootaxa, 2012)
(Erratum)